Accountable leaders inspire a culture where everyone steps up, takes ownership, and delivers results - Molinaro, Vince (Gildan Audio, 2020)
Leadership accountability is a major issue in organizations around the globe. Research has shown that teams and individual employees are overwhelmingly dissatisfied with the degree of accountability demonstrated by their leaders. Effective teams need responsible and accountable leaders-the solution seems simple. Yet, thousands of businesses are struggling with mediocre performance and widening gaps in leadership. This essential resource provides practical and no-nonsense strategies to transform any organization into a cohesive, highly motivated culture of accountable leaders and fully committed teams.Bestselling author Vince Molinaro shares his proven methods of optimal leadership accountability, providing a step-by-step blueprint for leaders in any organization. Developed from years of experience helping Fortune 500 companies build strong leaders and effective teams, this book will enable you to: build strong leadership accountability, understand why gaps in leadership occur and recognize accountability issues in your own organization, develop an effective strategy to install a culture of accountability and responsibility in your business, and identify and implement organizational practices that encourage accountable leadership throughout your management structure.